Children's Character Through Learning the Art of Musical Forming - Sritanto Sritanto (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
This study aims to describe and determine the implementation of 21st century character education, namely the ability to collaborate and the ability to communicate musically through children's songs. Qualitative descriptive method is used to generate data related to predetermined objectives through interview observation and documentation. The subjects of this study were teachers and students at SD Tamansiswa Yogyakarta. The data were analyzed using an interactive model consisting of data reduction, data presentation, and conclusion drawing. Due to the Covid 19 pandemic, the research cannot run properly (making face-to-face observations in the field). Thus, the research only took place through interviews with the art of music teacher at the school. The results of the research show that in the process of learning the art of music there are activities, and elements of musical rules that are beneficial for the formation of the character of students. The characters contained in learning the art of music can be capital in facing challenges in this 21st century era. Some of the character formations found in learning the art of music at SD Tamansiswa Yogyakarta are serious; firm; orderly/organized; togetherness/ collaboration; tolerance; self-confidence; discipline, obedient, patient; and comunication